The Effect of Giving Ginseng Tea on Anxiety During Premenopause in the Mekarjaya Village Area, Purwakarta Regency, Indonesia - Rosanti, Aan (HM Publisher, 2024)
Premenopause is a natural transition phase in women marked by hormonal changes that can cause a variety of symptoms, including anxiety. Ginseng is an herbal plant that has long been used to treat various diseases, including anxiety. This study aims to determine the effect of giving ginseng tea on anxiety during premenopause in the Mekarjaya Village area, Purwakarta Regency, Indonesia. This research uses a pre-experimental research design, with a one group pretest-posttest design. The research population was all premenopausal women in Mekarjaya Village, Purwakarta Regency, Indonesia. The research sample was 20 people, taken using purposive sampling technique. The measuring tool used is the Hamilton Anxiety Scale Questionnaire (HAMA). The results of the study showed that there was an effect of giving ginseng tea on reducing anxiety during premenopause. This can be seen from the results of the Wilcoxon test with p-value <0.05. The average HAMA score before giving ginseng tea was 25.45, while after giving ginseng tea it was 18.55. Based on the results of this study, it can be concluded that giving ginseng tea can reduce anxiety during premenopause.